(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the characteristics of threats affecting the security of Central Asian countries. Also in the article, complex global changes in the world have a serious impact on the Central Asian region and scientifically emphasizes the need for a systematic solution to large-scale problems within the framework of ensuring the national security of the countries of this region.